Measurements of the Higgs boson production cross section and couplings in the W boson pair decay channel in proton-proton collisions at s=13TeV - Tumasyan, A; Adam, W; Andrejkovic, J W; Bergauer, T; Chatterjee, S; Damanakis, K; Dragicevic, M; Escalante Del Valle, A; Hussain, P S; Jeitler, M; Krammer, N; Lechner, L; et al. (The European physical journal. C, Particles and fields, 2023)
Production cross sections of the standard model Higgs boson decaying to a pair of W bosons are measured in proton-proton collisions at a center-of-mass energy of 13TeV. The analysis targets Higgs bosons produced via gluon fusion, vector boson fusion, and in association with a W or Z boson. Candidate events are required to have at least two charged leptons and moderate missing transverse momentum, targeting events with at least one leptonically decaying W boson originating from the Higgs boson. Results are presented in the form of inclusive and differential cross sections in the simplified template cross section framework, as well as couplings of the Higgs boson to vector bosons and fermions. The data set collected by the CMS detector during 2016-2018 is used, corresponding to an integrated luminosity of 138fb-1. The signal strength modifier μ, defined as the ratio of the observed production rate in a given decay channel to the standard model expectation, is measured to be μ=0.95-0.09+0.10. All results are found to be compatible with the standard model within the uncertainties.